Mechanical characterization of additively-manufactured metallic lattice structures with hollow struts under static and dynamic loadings - Xiao, Lijun; Feng, Genzhu; Li, Shi; Mu, Keliang; Qin, Qinghua; Song, Weidong (International journal of impact engineering, 2022)
•Novel hollow lattice configurations are proposed and fabricated by SLM process.•Their specific energy absorption is superior to many existed lattices.•The two lattice configurations exhibit different strain rate sensitivity.•The anisotropy of hollow octet-truss lattice is insensitive to geometric parameter.•The FE simulations are in excellent agreement with the experimental results. Inspired by the natural hollow structures, periodic lattice structures composed of hollow struts and spheres were designed and fabricated by selective laser melting (SLM) process with 316L stainless steel. Two architecture configurations with Body-Centered Cubic (BCC) and Face-Centered Cubic (FCC) symmetry were taken into consideration. Finite element (FE) simulations based on representative volume element (RVE) models and cell-assembly models were conducted to investigate the elastic response and large deformation behavior of the hollow lattice materials, respectively. Afterwards, compression experiments were carried out on an electronic universal machine and a drop hammer (DH) system to explore the quasi-static and dynamic mechanical response of the lattice specimens. The complete deformation evolutions of the lattice samples under different loading velocities were captured through high-resolution photography and inspected by the digital imaging correlation (DIC) analysis. Both the experimental research and numerical simulations demonstrated that the hollow beam cross-sections contributed to the stable crushing response of the proposed lattice structures under either quasi-static or dynamic compression. Accordingly, the post-yield behavior of the tested lattice structures was quite smooth without any fluctuations. Meanwhile, the specific strength and energy absorption of the hollow lattice structures were found to be superior to many existed lattice materials with solid struts, and comparable with the reported triply periodic minimal surface (TPMS) lattice structures. Finally, the effect of the geometric characteristic parameters on the specific mechanical properties of the lattice structures was discussed according to the supplemental analysis by numerical simulations.